Comparison between experimental and simulated strain profiles in Ge channels with embedded source/drain stressors. Issue 11 (25th July 2014) - Bühler, R.; Eneman, G.; Favia, P.; Bender, H.; Vincent, B.; Hikavyy, A.; Loo, R.; Martino, J. A.; Claeys, C.; Simoen, E.; Collaert, N.; Thean, A.; et al.
Abstract Two planar Ge‐based MOSFET structures were analysed for n‐ and p‐type transistors with tensile and compressive strain implemented in the <110> channel direction using source/drain stressors. Strain profiles measured by nano‐beam diffraction (NBD) have been compared with Sentaurus process simulations. The TCAD simulations were tuned with the actual process using NBD measurements, resulting in a more realistic simulation and, therefore, a more reliable interpretation is now possible. dark‐field scanning transmission electron microscopy images added to the strain profiles returned interesting results about the Ge virtual substrate condition and how it disturbs the NBD readings due to the presence of extended defects in strain relaxed Ge buffer layers. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)